Influence of the small intertidal seagrass Zostera novazelandica on linear water flow and sediment texture - Wiebke M. Heiss; Abigail M. Smith; P. Keith Probert (New Zealand Journal of Marine and Freshwater Research, 2000)
The influence of a small intertidal seagrass, Zostera novaz.elandica (Setchell), on tidal current velocities and sediment texture was studied at Harwood, Otago Harbour, New Zealand. Tidal current velocities were substantially reduced inside the Z. novazelandica patch compared to velocities above the patch (3.7 times greater) and outside it (2.5 times greater), causing a low‐flow environment among the 12‐cm‐tall seagrass. Current velocities combined over one tidal cycle occupied a much wider range outside ( 1.2‐A.b cms ‐1 ) and above ( 1.9–7.1 cm s ‐1 ) the seagrass patch than inside (0.1–1.8 cm s ‐1 ) indicating slower and less variable water flow. Suspended mud ( novazelandica may reduce water flow and accumulate finer sediment sizes to a lesser extent than larger subtidal seagrass species.